Should legal professional privilege be absolute: a comparative appraisal - Shair Mohamad, Mohd Akram (LexisNexis, 2015)

(untitled)
Legal Professional privilege, a single integral (whose sub-heads are legal advice privilege and litigation privilege) is not a mere procedural incident of the forensic but a fundamental condition on which the administration of justice as a whole rests. It has been described as a fundamental human right of any person to obtain skilled advice by the law. The privilege exists to ensure that there is a full and frank disclosure between lawyers and their clients which helps to promote broader public interest in the observance of law and administration of justice. In England and Australia, the courts have recently held that the privilege is absolute subject only to the narrowly defined exception of cases where the client is seeking legal advice in order to enable himself to better commits a fraud of crime. The privilege is an enduring privilege, unless the client waives it expressly or impliedly. the absolutist view of the privilege has not been accepted in Canada. The position in India, Malaysia and Singapore courts have restrictively interpreted their codes, instating that legal professional privilege can only be waived by the client, expressly and in writing. this article seeks to briefly discuss the nature of both aspects of legal professional privilege, whether it should be absolute and can be waived only expressly.